Liquid alkali metals proceedings of the international conference organized by the British Nuclear Energy Society, held at Nottingham University on 4-6 April 1973 - Monro, Mary (British Nuclear Energy Society, 1973)
Proceedings of an international conference held at Nottingham University on 4-6 April 1973.